Anti-liver fibrosis of green materials Moringa oleifera seed oils from Madura Island against hepatocellular carcinoma development - Hendra Susanto; Ahmad Taufiq; Nik Ahmad Nizam Nik Malek; Wira Eka Putra (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.